Physical development of children consuming water with superoptimal fluorine concentration - Golebiowska, Maria; Łuczak, Bogdan; Grabowska, Jadwiga; Chlebna-Sokół, Danuta (Anthropological Review, 1982)
The material for this work has been collected in a settlement Błaszki (Central Poland in the vicinity of the city of Sieradz) known for occurence of endemic mottled teeth. 164 boys and 173 girls aged 7-10 years were examined by dentists, physicians and physical anthropologists. On grounds of occurence of changes in the enamel subjects were divided into two groups: affected and unaffected. In the case of children from Błaszki influence of general biocultural environment on affected and unaffected individuals is the same with one exception: fluorine concentration in drinking water. Affected children consume water with content of 2.68 mg of fluor per litre while the unaffected ones 0.05 - 0.88 mg F/I. This paper deals with 17 somatic characters elaborated with use of standard statistical procedures. Body proportions were evaluated with use of Perkal's indices. Analysis of somatic characters showed that overaboundance of fluorine in drinking water affects not only teeth but also influences physical development in general. Particular sensitivity concerns boys in periods of intense growth (7 and 10 years). It results in underdevelopment of many somatic characters, especially those related to body length. In girls changes are of the same direction but much weaker (differences between respective means are statistically insignificant).